(untitled) (Ahkam: Jurnal Hukum Islam, 2015)
In case of dispute settlement via the outside court, then offered several alternative dispute resolutions which give the ease with which the process is fast, cheap and resolved as well as possible, one of which uses the process of arbitration. Arbitration is the most interesting option in order to resolve the dispute in accordance with their wishes and needs. So, resolving disputes through arbitration is regulated specifically in Act No. 30/1999 regarding arbitration and alternative dispute resolution. In many civil agreement cases, arbitrate clause widely used as dispute for resolution options. Legal opinion given arbitration institutions are independent, final, and binding. Because of the opinions given will be the part that is inseparable from the agreement staples. Each of the opposite opinion against the opinion of the law means a violation of the Covenant (breach actions of contract-tort). Therefore resistance cannot be made in the form of any remedy. In this paper discusses about the arbitration as dispute resolution institutions according to act No. 30/1999 which include: understanding of arbitration, the arbitral seat as non litigation, pros and cons of arbitration dispute, the kind that become arbitration authority, implementation of the ruling of the arbitration and the strengths of arbitration decision. Kata kunci: Arbitrase, Lembaga Penyelesaian Sengketa, Undang-Undang No. 30 Tahun 1999